Anisotropic growth and structure-dependent photoresponse activity of multi-level one-dimensional PbS nano-architectures. Issue 67 (29th June 2016) - Zha, Chenyang; Pang, Chao; Xu, You; Ji, Cheng; Zhang, Xiaoyan; Shen, Liming; Wang, Yifeng; Gupta, Arunava; Bao, Ningzhong
Abstract : PbS nanostructures with three-fold hierarchy in 〈111〉 directions for designing optoelectronic devices. Abstract : In this work, hierarchical lead sulfide (PbS) nano-architectures were obtained via a simple one-pot hydrothermal method using a single-source precursor of Pb(ii )–thiourea complex, without involving any insulating organic surfactants. Structurally, the eight-armed hierarchical PbS nanostructures were controlled to exhibit one-fold, two-fold, or three-fold hierarchy of anisotropic growth along 〈111〉 directions, under different reaction conditions. The product morphology and structural evolution in the hydrothermal process exhibit four stages: Stage 1, the nucleation of PbS nanoparticles from the complex precursor; Stage 2, the formation of cubic PbS growth bases; Stage 3, the formation of PbS nano-architectures from consumption of the previously formed PbS growth bases; and Stage 4, the deconstruction of the hierarchical PbS nanoarchitectures. Nanostructures with high energy crystal faces are attractive for designing high efficiency solar cell devices. Within the PbS octa-armed dendrites, all sub-units grow along the 〈111〉 directions with 100 facets exposed. The photoexcited electrons can be driven in the 100 facets with mixed Pb/S atoms through σ bonding consisting of the overlapping s(Pb 6s)–p(S 3p) orbitals, which significantly shortens the carrier transfer distance and reduces the carrier recombination. Drop-cast thin films prepared with octa-armed PbS dendrites, showing desired [100] structural orientation, exhibit greatly enhanced photocurrent compared to that of spray-printed thin films without any structural orientation. It is expected that these findings will be useful in understanding the formation and application of PbS and other fcc nanocrystals with different morphologies.